1990
DOI: 10.1038/345727a0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of insulin-dependent diabetes mellitus in non-obese diabetic mice by transgenes encoding modified I-A β-chain or normal I-E α-chain

Abstract: Insulin-dependent diabetes mellitus (IDDM) is a disease with an autoimmune aetiology. The inbred non-obese diabetic (NOD) mouse strain provides a good animal model of the human disease and genetic analysis suggests that, as in man, at least one of the several genes controlling the development of IDDM is linked to the major histocompatibility complex. The NOD mouse does not express I-E owing to a deletion in the promoter region of the I-E alpha-chain gene, and the sequence of NOD I-A beta-chain in the first ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
191
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 333 publications
(198 citation statements)
references
References 19 publications
5
191
1
1
Order By: Relevance
“…Concordantly, treatment of NOD mice with anti-CD4 antibody abrogates disease (12,13). Introduction of MHC-II other than I-A g7 , the endogenous NOD MHC-II, also prevents diabetes, possibly by altering the CD4 ϩ T cell repertoire (14)(15)(16). Finally, the strong genetic linkage of disease to MHC-II provides a rationale for focusing on CD4 ϩ T cells (5,17,18).…”
mentioning
confidence: 99%
“…Concordantly, treatment of NOD mice with anti-CD4 antibody abrogates disease (12,13). Introduction of MHC-II other than I-A g7 , the endogenous NOD MHC-II, also prevents diabetes, possibly by altering the CD4 ϩ T cell repertoire (14)(15)(16). Finally, the strong genetic linkage of disease to MHC-II provides a rationale for focusing on CD4 ϩ T cells (5,17,18).…”
mentioning
confidence: 99%
“…This approach has several drawbacks. First, the DRB3 and DRB4 genes are omitted from consideration despite their importance in many immune responses (15,16) and the fact that even single chain MHC class II genes can profoundly influence expression of autoimmune disease such as IDDM (17)(18)(19). Second, expression of independent transgenes ignores the possibility that multiple genes in the class II region contribute to disease susceptibility through interactions during positive and negative selection of the T cell repertoire or through aspects of their peripheral coregulation (20,21).…”
mentioning
confidence: 99%
“…In the NOD model of autoimmune diabetes, numerous past reports have indicated that MHC heterozygosity results in protection from disease (9)(10)(11)(12)(13)(14). In fact, the presence of any other ␤57 Asp-expressing class II MHC, in addition to I-A g7 , results in markedly decreased incidence of diabetes; for example is the result of F1 mice derived from mating of wild type NOD (I-A g7 ) to NOD.GD (I-A d ), which are protected from diabetes (15).…”
mentioning
confidence: 99%